The walking dead. The complete third season [videorecording (DVD)]. - Lincoln, Andrew, 1973-; Holden, Laurie; Callies, Sarah Wayne, 1977- (Walking dead (TV series), 2013)
In a uncertain world, Rick Grimes and his band of survivors must not only fight the dead. In a sixteen episode season, Rick and his fellow survivors continue to seek refuge in a desolate and post-apocalyptic world and soon discover that there are greater forces to fear than just the walking dead. The struggle to survive has never been so perilous. Introducing new characters: the Governor and fan-favorite Michonne, along with her zombie pets.